La teoría del equilibrio económico y financiero de los contratos administrativos en Costa Rica - López Jiménez, Enrique (2014)
This study examines the application of the principle of economic and financial equilibrium of administrative contracts in Costa Rica. Special emphasis is put on jurisprudence of the Constitutional Chamber of the Supreme Court of Justice. This study analyzes five major issues: (1) Normative foundations. (2) The introduction of the concept of risk in the contractual relationship. (3) The materialization of the principle of economic equilibrium (principles of risk and responsibility, factum principis, ius variandi, sujétions imprévues, théorie de l’imprévision, price or tariff adjustment). (4) Adjustment methodologies. (5) Remedy processes.